2011
DOI: 10.1016/j.jvs.2010.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Arch and visceral/renal debranching combined with endovascular repair for thoracic and thoracoabdominal aortic aneurysms

Abstract: The hybrid procedure is associated with acceptable rates of mortality and paraplegia when used for treatment of arch/proximal descending thoracic/TAAA. These results support this procedure as a reasonable approach to a difficult surgical problem; however, longer follow-up is required to appraise its ultimate clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…[32][33][34] In studies in which patients are more likely to undergo a staged procedure, some authors have demonstrated that mortality and neurologic deficits approach those of TEVAR alone. 35 Conflicting data are found when TEVAR with aortic debranching is compared to open surgical repair. Some evidence suggests that the two populations have equivalent mortality and neurologic deficit rates, with the hybrid operation cohort having a significantly increased reintervention rate.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] In studies in which patients are more likely to undergo a staged procedure, some authors have demonstrated that mortality and neurologic deficits approach those of TEVAR alone. 35 Conflicting data are found when TEVAR with aortic debranching is compared to open surgical repair. Some evidence suggests that the two populations have equivalent mortality and neurologic deficit rates, with the hybrid operation cohort having a significantly increased reintervention rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although open repair is an effective and durable option for patients with JAA, particularly in centers of excellence for patients at low physiologic risk, 7,8 fenestrated and branched EVAR (FBE) in other parts of the world have emerged as effective, potentially less invasive alternatives. [9][10][11] In the United States, however, lack of widespread availability of FBE has allowed other techniques to emerge, namely open debranching, [12][13][14] homemade fenestrations, 15 and the "snorkel" or "chimney" configuration.…”
mentioning
confidence: 99%
“…Mortality rates are higher when 3 or more vessels are reconstructed 10 . However, visceral graft patency range from 85% to 97% in more than a year follow-up in large series [10][11][12] . This minimally invasive surgical approach offers a possible alternative treatment option for patients who are un t for the open repair or who have unfavourable anatomy for total endovascular repair 13 .…”
Section: Discussionmentioning
confidence: 99%